STUDI MAQASHID ASY-SYARIAH ATAS PERISTIWA PIDANA: PELECEHAN SEKSUAL MELALUI MEDIA ELEKTRONIK DALAM PENAGIHAN UTANG-PIUTANG FINTECH ILEGAL (Journal of Islamic Law Studies, 2020)
The rise and implementation of Fintech is a result of the formation of lifestyle and consumptive behavior. This pattern of consumption behavior bases the use of commodities on desire and not on need. This happens because people continually want to complete their desire to own or use something that is beyond their needs even though they are still financially unable. One of the behaviors was exploited by Fintech, which provides financing services illegally. Illegal Fintechs are considered dangerous because they are not subject to and comply with existing regulations so that the potential deviation in the implementation process can be a threat to customers or people around the customer. The threat was born because the organizers of the illegal Fintech were ultimately not under the supervision of the relevant authorities, so that customers and the public also had difficulty monitoring and classifying legal Fintech and illegal Fintech. These problems are analyzed using the perspective of the Maqashid ash-Shariah study. This research is based on the YI case study where loan collection is done involving sexual harassment of the person concerned. This research was conducted based on literature search and media search. This research found that at least the problem is related to at least two aspects of Maqashid ash-Sharia, namely damage to the maintenance of the soul and reason.